2012
DOI: 10.1107/s0907444912042175
|View full text |Cite
|
Sign up to set email alerts
|

Structures of an active-site mutant of a plant 1,3-β-glucanase in complex with oligosaccharide products of hydrolysis

Abstract: Plant endo-1,3-β-glucanases are involved in important physiological processes such as defence mechanisms, cell division and flowering. They hydrolyze (1→3)-β-glucans, with very limited activity towards mixed (1→3,1→4)-β-glucans and branched (1→3,1→6)-β-glucans. Here, crystal structures of the potato (Solanum tuberosum) endo-1,3-β-glucanase GLUB20-2 with the nucleophilic Glu259 residue substituted by alanine (E259A) are reported. Despite this active-site mutation, the protein retained residual endoglucanase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Research on GHL17 protein structure revealed two strictly conserved glutamate residues that act as the proton donor and the nucleophile in all reactions catalyzed by glycosyl hydrolases (Jenkins et al, 1995; Wojtkowiak et al, 2013). A number of aromatic and hydrophilic residues located near the catalytic cleft, presumably involved in substrate specificity and enzyme activity, are also conserved among all plant GHL17 proteins (Wojtkowiak et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on GHL17 protein structure revealed two strictly conserved glutamate residues that act as the proton donor and the nucleophile in all reactions catalyzed by glycosyl hydrolases (Jenkins et al, 1995; Wojtkowiak et al, 2013). A number of aromatic and hydrophilic residues located near the catalytic cleft, presumably involved in substrate specificity and enzyme activity, are also conserved among all plant GHL17 proteins (Wojtkowiak et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A number of aromatic and hydrophilic residues located near the catalytic cleft, presumably involved in substrate specificity and enzyme activity, are also conserved among all plant GHL17 proteins (Wojtkowiak et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this system, laminarin must first be debranched by a GH30 exo-␤(1,6)-glucosidase before being hydrolyzed by a GH17 endo-␤(1,3)-glucanase, which has very low activity on ␤(1,6)-glucose-branched laminarin (55). In general, GH17 endoglucanases have a very narrow active-site cleft that does not effectively accom- (47,55). This is unlike BuGH16 and BuGH158 enzymes, which allow the 1,3GUL system to bypass the initial debranching requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Some oligosaccharides are biologically active substances that possess antimicrobial activity, immunoenhancing ability, antitumor activity (Fang et al, 2012; Zou et al, 2016; Chen et al, 2017), and antioxidant activity (Chen et al, 2015; Malunga and Beta, 2015; Hamley-Bennett et al, 2016) and have great potential in nutrition (Kashtanova et al, 2016; Marcotuli et al, 2016), health care (Mensink et al, 2015; Zhang et al, 2016; Di et al, 2017), disease diagnosis, and control (Kazłowski et al, 2012; Zhang et al, 2016). To date, oligosaccharides derived from plants and chitins have been used widely (Wojtkowiak et al, 2013; Hamley-Bennett et al, 2016; Yin et al, 2016). On the other hand, algae, an inexpensive and abundant biomass, is attracting increasing attention because it can be used for the production of algae oligosaccharides that have better physiological activity and a higher value than algae polysaccharides (such as agar, carrageenan, and alginate).…”
Section: Introductionmentioning
confidence: 99%